2017
DOI: 10.1515/mipo-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Pb(II) and Mo(VI) Removal by Kaolinite Impregnated with Zero-Valent Iron Particles

Abstract: Abstract. In this work, kaolinite modified with zero-valent iron was synthesized and used as a sorbent for Pb(II) and Mo(VI) removal from aqueous solutions. The obtained material was characterized by X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. The methods revealed successful modification by the Fe 0 particles precipitation on the surface of well-ordered kaolinite. The sorption experiment results showed a significant increase of sorption capacity in relation to the raw kaolinite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…An increase in the intensity of the basal spacing could be observed in both 10% and 25% KZVIs at 2.03 Å. However, the increment was noticed to be more prominent in 25% KZVI than in 10%, and these trends were quite similar to those earlier reported by Üzüm et al [22] and Rybka et al [20]. Rybka et al [20] also reported the presence of zerovalent iron at basal spacing of 2.92 Å and 2.03 Å, which was observed to be featureless in the 10% modified adsorbents but quite prominent in the 25% adsorbents.…”
Section: Characterization Of Kaolin and Modified Adsorbentssupporting
confidence: 90%
See 3 more Smart Citations
“…An increase in the intensity of the basal spacing could be observed in both 10% and 25% KZVIs at 2.03 Å. However, the increment was noticed to be more prominent in 25% KZVI than in 10%, and these trends were quite similar to those earlier reported by Üzüm et al [22] and Rybka et al [20]. Rybka et al [20] also reported the presence of zerovalent iron at basal spacing of 2.92 Å and 2.03 Å, which was observed to be featureless in the 10% modified adsorbents but quite prominent in the 25% adsorbents.…”
Section: Characterization Of Kaolin and Modified Adsorbentssupporting
confidence: 90%
“…However, the increment was noticed to be more prominent in 25% KZVI than in 10%, and these trends were quite similar to those earlier reported by Üzüm et al [22] and Rybka et al [20]. Rybka et al [20] also reported the presence of zerovalent iron at basal spacing of 2.92 Å and 2.03 Å, which was observed to be featureless in the 10% modified adsorbents but quite prominent in the 25% adsorbents. The lack of shift of the 7.2 Å basal spacing of the modified adsorbents indicated that ZVI particles were synthesized exclusively on the kaolin and intercalation did not occur.…”
Section: Characterization Of Kaolin and Modified Adsorbentssupporting
confidence: 89%
See 2 more Smart Citations